Phytoprotective and growth-regulatory properties of metabolic bioformulations on the base of soil streptomycetes - Biliavska, L. O.; Kozyritska, V. E.; Kolomiets, Yu. V.; Babich, A. G.; Iutynska G. О. (Reports of the National Academy of Sciences of Ukraine, 2015)
New bioformulations for the plant growing on the base of metabolites of soil streptomycetes are developed. It is shown that new bioformulations have a positive impact on rhizosphere microbiota and the general biological activity of soil, suppress the development of plant parasitic nematodes, stimulate the growth of tomatoes, and increase the yield and its quality.